Clash of Drought Narratives: A Study on the Role of Small Reservoirs in the Emergence of Drought Impacts - Germano G. Ribeiro Neto; Lieke A. Melsen; Alexandre C. Costa; David W. Walker; Louise Cavalcante; Sarra Kchouk; João Paulo Brêda; Eduardo S. P. R. Martins; Pieter R. vanOel (Earth's Future)
Abstract In regions characterized by a high concentration of small reservoirs, there is often public debate about the effectiveness of these structures in locally adapting to and mitigating drought impacts, bearing in mind their potential to modify or induce drought events in downstream areas. In this study, we investigated the influence of a Dense Network of Small Reservoirs (DNR) on the emergence and intensification of drought impacts at catchment scale, as well as their local social benefits. This analysis was based on the Socio‐Hydrological‐Agricultural‐Reservoir (SHARE) model, specially developed for this purpose, with a medium‐sized catchment in the semi‐arid region of Brazil as a case study. We identified that, while a DNR can prolong the effects of a hydrological drought on storage in a large strategic reservoir at the catchment outlet by obstructing surface‐runoff connectivity, it plays a crucial role in mitigating drought impacts at a local level. Specifically, the presence of small reservoirs has the potential to boost local agricultural production by up to 5 times compared to scenarios without these structures. In addition, our simulation results suggest there is a notable reduction in the need for emergency water distribution by water trucks in the presence of a DNR. This study highlights the need for a balanced approach to implementing public policies, weighing the local benefits of small reservoirs against the possible downstream impacts on large reservoirs.